Rock glaciers of the Beartooth and northern Absaroka ranges, Montana, USA. (16th September 2019) - Seligman, Zachary M.; Klene, Anna E.; Nelson, Frederick E.
Abstract: Six hundred sixty‐one rock glaciers in the northern Absaroka and Beartooth Ranges of south‐central Montana were digitized and evaluated using geographic information systems technology and an array of topographic and environmental parameters. Beartooth rock glaciers are larger, occur at higher elevations, receive more precipitation, and are subject to lower temperatures than northern Absaroka rock glaciers. Elevation is strongly correlated with rock glacier activity. Comparative analysis of these adjacent mountain ranges indicates that Beartooth geomorphic landscapes are shifting from predominantly glacial to periglacial regimes, and that the northern Absarokas have largely completed this transition. Because glaciers are declining in response to climate warming, rock glaciers could soon become the most important source of ice in the region.